Pengaruh Konten Youtube Fiersa Besari “Atap Negeri” terhadap Sikap Mahasiswa Pecinta Alam dalam Melestarikan Lingkungan - Milda Irnadianis Ipada; Alfi Satria; Wiena Safitri (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
In the millennial era, Youtube has become a promising field of work, as can be seen in one of the content creators named Fiersa Besari, besides being a writer and musician, Fiersa is also a Youtube content creator with 3.2 million subscribers. On her personal channel, Fiersa takes on the topic of nature and creates a grand adventure through the project "Ekspedisi Atap Negeri: 33 Mountains in 33 Provinces", hoping to be a source of inspiration. This content contains vlogs about climbing 33 mountains in 33 provinces in Indonesia, thus raising environmental issues as moral problems related to human behavior. This study then examines the effect of Fiersa Besari's Youtube content "Atap Negeri" on the attitude of nature lovers students in preserving the environment. This research uses a quantitative approach with a sampling technique using probabbility sampling, which is carried out by random sampling technique, and data collection is carried out using a questionnaire. This study concluded that there is a positive influence as evidenced in the results of the correlation analysis test as well as hypothesis testing with non-parametric statistics using spearman rank, with a significance value of 0.003 which means <0.05, thus rejecting H0 and Ha failed to reject. However, at the level of relationship between variables, a correlation coefficient of 0.373 is obtained, which means that the level of relationship is low.